Muros e pontes? políticas públicas e arte na periferia - Stockmans, Idalzi (My University, 2022)
This dissertation is the result of research involving the themes periphery, art and fomentation,considering current movements and affirmative actions. It has as general objective to verifythe difficulties and possibilities of access for artists and cultural agents living in the urbanperiphery of Caxias do Sul - RS to the public mechanisms of cultural fomentation. In this way, the research problem was defined as: What are the difficulties and possibilities for artists and cultural agents living in the urban periphery of Caxias do Sul, in the sense of access to the public mechanisms of cultural fomentation? The theoretical foundation has as base contemporary thinkers, such as Ermínia Maricato (2013), Augusto Boal (2009), Paulo Freire (1987-2000), Boaventura Santos (2018), Denise Carreira (2018), amongst others, interlinking the ideas of art, public policies, and urban periphery. In methodological terms, this work associates bibliographical revision; document analysis; multiple investigative approximations with the research subjects, in workshop interactions, spectacles, meetings; planning and publication of the Uno-me edict, coordination of the interactions resulting from this edict; production and vehiculation of depositions, biographical accounts of the cultural agents that were born and reside in the urban periphery of Caxias do Sul; and interviews. Through the realization of the Uno-me edict, 14 artists were contemplated. To answer our problem, we have built a history of investment on cultural fomentation mechanisms, on the part of public power of Caxias do Sul, since the creation of the Municipal Culture Secretariat, in 1997, until 2020 and we have analysed other public documents linked to the city?s culture. We conclude through this investigation that affirmative actions referring to culture, on part of public power, applied to the urban periphery are urgent and imperative, to promote social equity, but must be built through the listening to the subjects demands, inhabitants of each territory. [resumo fornecido pelo autor]
Esta dissertação é resultado de pesquisa envolvendo os temas periferia, arte e fomento, considerando movimentos e ações afirmativas atuais. Tem, como objetivo geral, verificar dificuldades e possibilidades de acesso dos artistas e agentes culturais moradores da periferia urbana de Caxias do Sul - RS, aos mecanismos públicos de fomento à cultura. Neste sentido, o problema da pesquisa ficou assim definido: Quais as dificuldades e possibilidades dos agentes culturais moradores da periferia urbana de Caxias do Sul - RS, no sentido de acesso aos mecanismos públicos de fomento à cultura? A fundamentação teórica tem como base pensadores contemporâneos, como Ermínia Maricato (2013), Augusto Boal (2009), Paulo Freire (1987-2000), Boaventura Santos (2018), Denise Carreira (2018), entre outros, entrelaçando ideias de arte, políticas públicas e periferia urbana. Em termos metodológicos, o trabalho associa revisão bibliográfica; análise de documentos; múltiplas aproximações investigativas com os sujeitos da pesquisa, em interações de oficinas, espetáculos, reuniões; planejamento e publicação de edital Uno-me, coordenação das interações decorrentes deste edital; produção e veiculação de depoimentos, relatos biográficos dos agentes culturais nascidos e residentes na periferia urbana de Caxias do Sul; e entrevistas. A partir da realização do edital Uno-me, foram contemplados 14 artistas. Para responder ao nosso problema, construímos um histórico de investimentos em mecanismos de fomento à cultura, por parte do poder público de Caxias do Sul, desde a criação da Secretaria Municipal da Cultura, em 1997, até 2020, e analisamos outros documentos públicos vinculados à cultura da cidade. Concluímos a partir desta investigação que ações afirmativas referentes à cultura, por parte do poder público, aplicadas às periferias urbanas são urgentes e imprescindíveis, para promover a equidade social, mas devem ser construídas a partir da escuta das demandas dos sujeitos, habitantes de cada território. [resumo fornecido pelo autor]
Keywords: Cultura; Política cultural; Arte; Periferias - Caxias do Sul (RS); Culture; Cultural policy; Art; Inner cities - Caxias do Sul (Brazil)